2008
DOI: 10.1371/journal.pmed.0050147
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Intermediate Syndrome Following Acute Organophosphate Poisoning: A Prospective Cohort Study from Sri Lanka

Abstract: BackgroundIntermediate syndrome (IMS) is a major cause of death from respiratory failure following acute organophosphate poisoning. The objective of this study was to determine repetitive nerve stimulation (RNS) predictors of IMS that would assist in patient management and clinical research.Methods and FindingsSeventy-eight consenting symptomatic patients with organophosphate poisoning were assessed prospectively with daily physical examination and RNS. RNS was done on the right and left median and ulnar nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 29 publications
(44 reference statements)
0
60
0
1
Order By: Relevance
“…Although it was recommended to calculate the changes in CMAP size between the first and the fourth or the fifth response of a train of stimuli (15) we took the second response as well, since Maselli et al (2004) and Jayawardana et al (2008) observed the maximum decrement at the second stimulus (27,31). The data set of the current study showed the maximum decrement either at the second or the third stimulus.…”
Section: ++mentioning
confidence: 73%
See 1 more Smart Citation
“…Although it was recommended to calculate the changes in CMAP size between the first and the fourth or the fifth response of a train of stimuli (15) we took the second response as well, since Maselli et al (2004) and Jayawardana et al (2008) observed the maximum decrement at the second stimulus (27,31). The data set of the current study showed the maximum decrement either at the second or the third stimulus.…”
Section: ++mentioning
confidence: 73%
“…NMJ dysfunction has been demonstrated by fast repetitive nerve stimulation with OP poisoning before clinical recovery (27), but there is no evidence whether these changes persist over the long term.…”
Section: Reviewsmentioning
confidence: 99%
“…However, in some cases muscle paralysis occurs24 to 96 hours after OP ingestion (intermediate syndrome), and this weakness, characteristic of IMS, may lead to respiratory failure and death. [5] MECHANISM OF ACTION: (Irreversible binding and permanent enzyme inactivation (aging). The mechanism of action of OP compounds that has well been known for more than 70 years, is the inhibition of cholinesterase.…”
Section: Discussionmentioning
confidence: 99%
“…The neurodegeneration observed commonly in organophosphate toxicity in hippocampus, pyriform cortex and amygdala may cause these delayed cognitive effects. The increased level of ACh in the synaptic cleft for a long duration may also be considered as the reason for this syndrome [14,15] .…”
Section: Mechanism Of Action and Clinical Symptomsmentioning
confidence: 99%